Grammar Girl's quick and dirty tips for better writing - Fogarty, Mignon (New York : Henry Holt and Co., 2008)
The founder of a popular weekly podcast shares comprehensive explanations for troublesome grammar rules in a resource complemented by memory tricks, word-choice guidelines, and e-mail tips.
Dirty words -- Grammar Girl on grammar! -- Let's get it started: starting a sentence -- Punch up your punctuation -- Big and tall: capitalization -- Prozac for pronouns: getting the stuntmen of language under control -- Internet intervention! -- I'm so stylish: style and writing -- Work it.
Includes bibliographical references (p. [203]-204) and index.
Keywords: English language -- Grammar; English language -- Rhetoric; Report writing; English language -- Grammar; English language -- Rhetoric; Report writing